Metode Peramalan Permintaan Jasa Penerjemahan Bahasa Asing Dengan Algorithma Linear Regression, Menggunakan Rapidminer. Studi Kasus : Azzam Translator Bekasi - Warsino Warsino (The Faculty of Science and Technology, 2017)
Along with the world’s business progress nowadays, businessrelationships between countries are no longer limited by territory. Thisprovides an economical value for those who carefully see the chances.One of the chances is foreign language translation business. As anyother businesses, a foreign language translation business should face some problems. One of the causes of the problems is: a foreign languagetranslation company cannot predict the volumes of orders of comingyears, which make them should employ translators on a part-time basis.As a result, the company frequently losses chances to obtain big orders.For that reason, it is required a method to assist the company inpredicting the volumes of sales. Linear Regression is one of the methodsby using data mining that has the capability to predict the datasets ofprevious years. By using the Linear Regression method and a tool namedRapidminer 8.1, a research successfully proves that a volume oftranslation order can be promptly acknowledged, seen from the RMSE(Root Mean Square Error) score at the amount of 0.823.